The impact of hostile abortion legislation on the United States maternal mortality crisis: a call for increased abortion education - Kheyfets, Anna; Dhaurali, Shubhecchha; Feyock, Paige; Khan, Farinaz; Lockley, April; Miller, Brenna; Cohen, Lauren; Anwar, Eimaan; Amutah-Onukagha, Ndidiamaka (Frontiers in Public Health, 2023)
The growing restrictive abortion policies nationwide and the Supreme Court decision on Dobbs v. Jackson Women's Health Organization place increasing barriers to abortion access in the United States. These restrictions disproportionately affect low-income people of color, immigrants, and non-English speakers, and have the potential to exacerbate already existing racial inequities in maternal and neonatal outcomes. The United States is facing a Black maternal health crisis where Black birthing people are more than twice as likely to experience maternal mortality and severe maternal morbidity compared to White birthing people. Restrictions creating geographic, transportation, and financial barriers to obtaining an abortion can result in increased rates of maternal death and adverse outcomes across all groups but especially among Black birthing people. Restrictive abortion laws in certain states will decrease already limited training opportunities in abortion care for medical professionals, despite the existing abortion provider shortage. There is an immediate need for federal legislation codifying broad abortion care access into law and expanding access to abortion training across medical education. This commentary explores the impact of restrictive abortion laws on the Black maternal health crisis through multiple pathways in a logic model. By identifying current barriers to abortion education in medical school and residency, we created a list of action items to expand abortion education and access.